Diagnostic work-up of bile duct strictures: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Facciorusso, Antonio; Crinò, Stefano Francesco; Gkolfakis, Paraskevas; Spadaccini, Marco; Arvanitakis, Marianna; Beyna, Torsten; Bronswijk, Michiel; Dhar, Jahnvi; Ellrichmann, Mark; Gincul, Rodica; Hritz, Istvan; Kylänpää, Leena; Martinez-Moreno, Belen; Pezzullo, Martina; Rimbaş, Mihai; Samanta, Jayanta; van Wanrooij, Roy L.J.; Webster, George; Triantafyllou, Konstantinos (Endoscopy, 2024)
1 ESGE recommends the combination of endoscopic ultrasound-guided tissue acquisition (EUS-TA) and endoscopic retrograde cholangiopancreatography (ERCP)-based tissue acquisition as the preferred diagnostic approach for tissue acquisition in patients with jaundice and distal extrahepatic biliary stricture in the absence of a pancreatic mass.2 ESGE suggests that brushing cytology should be completed along with fluoroscopy-guided biopsies, wherever technically feasible, in patients with perihilar biliary strictures.3 ESGE suggests EUS-TA for perihilar strictures when ERCP-based modalities yield insufficient results, provided that curative resection is not feasible and/or when cross-sectional imaging has shown accessible extraluminal disease.4 ESGE suggests using standard ERCP diagnostic modalities at index ERCP. In the case of indeterminate biliary strictures, ESGE suggests cholangioscopy-guided biopsies, in addition to standard ERCP diagnostic modalities. Additional intraductal biliary imaging modalities can be selectively used, based on clinical context, local expertise, and resource availability.